2016
DOI: 10.4236/ojg.2016.611104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Type Used in Tunneling on Land Subsidence and Mobility Effective Time under Different Earthquake Records

Abstract: During recent decades, tunnels construction in urban environments has been recognized as a useful factor in improving transportation situation in cities. Construction of underground structures like tunnels has a direct impact on the above-ground structures. The most important impacts are soil crust movement of the structure movement), acceleration change of the earthquake on structures, and land subsidence. The present research aims at seismic evaluation of the effect of soil type in land subsidence and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Also, different studies about affection of surface slope on surface displacement by deep and shallow tunneling and soil type's impact in tunneling on land subsidence and mobility effective time under dynamic loads have been performed by Rostami et al, based on their results it can be mention that in static and dynamic modes, with increase in surface slope, the vertical subsidence on top of tunnels would increase, also due to reduction of tunnel excavation, the depth is inversely related to the subsidence. And in soil type's impact case, record type and tunnel type have direct effect on effective placement duration (Rostami, Alielahi, Zare & Haghighi, 2016;Rostami, Firoozfar, Adhami, & Asghari, 2016). Rostami et al showed that application of umbrella arc as a supporting structure could cause a reduction in land subsidence and an implication the stability of tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Also, different studies about affection of surface slope on surface displacement by deep and shallow tunneling and soil type's impact in tunneling on land subsidence and mobility effective time under dynamic loads have been performed by Rostami et al, based on their results it can be mention that in static and dynamic modes, with increase in surface slope, the vertical subsidence on top of tunnels would increase, also due to reduction of tunnel excavation, the depth is inversely related to the subsidence. And in soil type's impact case, record type and tunnel type have direct effect on effective placement duration (Rostami, Alielahi, Zare & Haghighi, 2016;Rostami, Firoozfar, Adhami, & Asghari, 2016). Rostami et al showed that application of umbrella arc as a supporting structure could cause a reduction in land subsidence and an implication the stability of tunnel.…”
Section: Introductionmentioning
confidence: 99%